2011
DOI: 10.1164/rccm.201101-0093oc
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil in Pulmonary Arterial Hypertension

Abstract: Vardenafil is effective and well tolerated in patients with PAH at a dose of 5 mg twice daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(61 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…1). 59,1331 As ARIES-1 and ARIES-2 were reported in one article, 25 RCTs were included. 24 Among them, 11 assessed the effects of ERAs, seven assessed the effects of PDE-5Is, five assessed the effects of prostacyclin analogues, two assessed the effects of prostacyclin receptor agonists, and one assessed the effects of sGCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). 59,1331 As ARIES-1 and ARIES-2 were reported in one article, 25 RCTs were included. 24 Among them, 11 assessed the effects of ERAs, seven assessed the effects of PDE-5Is, five assessed the effects of prostacyclin analogues, two assessed the effects of prostacyclin receptor agonists, and one assessed the effects of sGCs.…”
Section: Resultsmentioning
confidence: 99%
“…5,8,9,1524,26,29 In the other five trials that did not report this endpoint as defined, we extracted the data according to the definition. 16,25,27,30,31 If the study did not report all the relevant endpoints of clinical worsening, we combined the reported endpoints together as clinical worsening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It differs from already marketed PDE-5 inhibitors by having a short effective time and slight longer half life than that of sildenafil. The EVALUATION study by Jing et al, which sought out to demonstrate safety and efficacy of Vardenafil showed that it is well tolerated in twice daily dosing and showed a increase in 6MWD, and cardiac index, along with an decrease in mean pulmonary arterial pressure and pulmonary vascular resistance [51].…”
Section: Future Medicationsmentioning
confidence: 99%